Boisterous Mobs and Violated Borders: American Pugilistic Excursions to Ontario-1855 - 1881 - Manning, Richard (Ontario History, 2024)
The illegal status of prize-fighting in mid-nineteenth century United States led promoters in the North-East to find locations where matches could be conducted without interference from the authorities. With its relatively low population and easy lake access, Canadian territory along the north shore beaches of Lake Erie proved ideal. On nearly a dozen occasions between 1855 and 1881, thousands of ship-borne spectators navigated the lake to watch championship matches in Canada. This study examines peripheral elements of the matches: the experiences of spectators and the press, and the efforts in both countries to enforce the law. The events present two related areas for analysis. Firstly, the press’ depiction of the spectators provides insight into contemporary ideas about how “polite” society viewed fight enthusiasts. Secondly, while the events exposed and exploited the permeability of the border, they also provoked responses that strengthened it. Ultimately, violent fights, the mob-like behaviour of the crowds, and the flagrant violation of Canadian sovereignty forced governments to respond.